Intergenerational Persistence in Latent Socioeconomic Status: Evidence from Sweden and the United States - Vosters, Kelly; Nybom, Martin (Journal of Labor Economics, 2017)
Recently Gregory Clark and coauthors have argued that social mobility rates are constant across countries and lower than traditionally estimated, hypothesizing that prior estimates of intergenerational persistence are attenuated from focusing on a single proxy for underlying status. We test this proposition by incorporating multiple proxy measures into a “least-attenuated” estimate of persistence for Sweden and conducting a Sweden–United States comparison. We find no evidence of substantial bias in prior estimates or of similarity across countries. We further extend our analysis to mothers, finding that additional measures improve the ability to capture transmission from mothers to both sons and daughters.